“Time Has Caught on Fire:” Eco-Anxiety and Anger in Selected Australian Poetry - Kowalcze-Pawlik, Anna (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
This essay discusses fire as a significant factor shaping Australian social and cultural life. It focuses first on the climate-change induced emotions such as eco-anxiety and anger that can be tied with the Australian landscape, and then moves on to a discussion of the presence and function of fire in selected contemporary Australian poetry. The reflection on the poetics of trauma in the second part of the essay is accompanied by a discussion of solastalgia connected with land dispossession as an experience of the First Nations expressed in the Aboriginal literature in English.